Estimation of Price Spread and Marketing Efficiency of Brinjal in Different Marketing Channels: A Case Study - Dwibedy, Soumya Kanta (Indian Journal of Marketing, 2013)
Efficient marketing plays an important role in increasing the producer's share in consumer's rupee and maintains the tempo of increased production. In the present study, the cost of cultivation, profit, price spread and marketing efficiency in the marketing of Brinjal in Khurdha district of Odisha were examined during the period from 2011-2012. Primary data were collected from 80 farmers through personal interview method using a specially designed pre- tested schedule. Three market channels were identified in the study area. These were Channel I: Farmer - Commission Agent-Wholesaler- Retailer- Consumer; Channel II: Farmer- Wholesaler- Retailer- Consumer and Channel III: Farmer- Organized Food Retail Chain-Consumer. The major findings revealed that the producer's share in consumer's rupee was 64.87 percent for Channel III, 49.85 percent for Channel II and 47.69 percent for Channel I. Channel III was found to be the most efficient market both by Shepherd's method and Acharya's method.